IOU field reports form, Douglas C. Harr, December 2, 1996 - Harr, Douglas C.et al (1996)
List of birds and locations contributed by Douglas C. Harr. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed